2016
DOI: 10.1111/ene.13217
|View full text |Cite
|
Sign up to set email alerts
|

Onset and evolution of anxiety in Parkinson's disease

Abstract: Anxiety is highly prevalent in PD. Higher anxiety scores over time and future development of anxiety are associated with female gender, cognitive impairment, autonomic dysfunction, insomnia and EDS. Anxiety and depression usually coexist and share similar determinants, suggesting a common pathophysiological mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
38
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 29 publications
(72 reference statements)
13
38
2
1
Order By: Relevance
“…Five variables are identified as predictor for anxiety in PD including sex, HAMD score, RBD-HK score, SCOPA-AUT score and SN echogenic areas in this study. In accordance with those previously reported in general non-parkinsonian populations [ 17 ], female was also considered an established risk factor for anxiety in patients with PD [ 11 , 12 , 52 , 53 ]. This finding may account for biological factors (such as hormonal changes), psychological and social factors such as greater stress when encountering life’s adversities like PD [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Five variables are identified as predictor for anxiety in PD including sex, HAMD score, RBD-HK score, SCOPA-AUT score and SN echogenic areas in this study. In accordance with those previously reported in general non-parkinsonian populations [ 17 ], female was also considered an established risk factor for anxiety in patients with PD [ 11 , 12 , 52 , 53 ]. This finding may account for biological factors (such as hormonal changes), psychological and social factors such as greater stress when encountering life’s adversities like PD [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…Jiang SM, et al compared dysautonomia in 99 patients with and without clinically relevant anxiety by HARS and the Non-Motor Symptoms Questionnaire (NMSQT) and found urinary disorder was the factors for anxiety in PD [ 54 ]. A longitude study in Europe also found an association between anxiety and dysautonomia [ 53 ]. The role of central noradrenergic dysregulation may play a role in both dysautonomia and anxiety [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address these questions, Zhu et al . assessed a wide range of variables potentially associated with anxiety symptoms in over 400 PD patients evaluated annually for 5 years.…”
supporting
confidence: 63%
“…Yet the factors associated with the onset and worsening severity of anxiety in PD are poorly understood. To address these questions, Zhu et al [3] assessed a wide range of variables potentially associated with anxiety symptoms in over 400 PD patients evaluated annually for 5 years.…”
mentioning
confidence: 99%
“…The world‐wide prevalence of Parkinson disease (PD) is rising steadily as the global population ages and significant advances are being made in the understanding of pathogenesis and treatment . It is of interest that in Portugal, where there is a high prevalence of LRRK2 G2019S mutation in PD, a recent study found PD prevalence to be 0.24% of those aged >50 years, with a total of 180/100 000 population, rather lower than might be expected, although this is probably explained by methodological issues .…”
mentioning
confidence: 99%